ANALISIS PENGARUH INFLASI DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KERINCI - Dewi Ernita (Bussman Journal : Indonesian Journal of Business and Management, 2021)
Regional development as an integral part of national development. The dependence of regional government funds on the central government also reflects the  government's  limited  ability  to  accumulate  Regional  Original  Revenues (PAD). To improve the implementation of development funds for the provision of community  services  and  to  increase  economic  growth  in  the  regions,  it  is necessary to provide adequate local sources and income. Inflation is one of the important   economic   indicators   that   can   provide   information   about   the development  of  prices  of  goods  and  services  paid  by  consumers.  Kerinci Regency's Regional Original Revenue (PAD) has increased every year along with the increase in GRDP accompanied by fluctuations in inflation due to economic growth that occurred in Kerinci Regency. This study is to determine the effect of inflation and GRDP on Original Income in Kerinci Regency. The data used are secondary data where the regression analysis method becomes the analysis tool used. The results of the study, GDP and inflation affect Kerinci regency's Original Regional Revenue